Risk management in the environmental management system of an oil refinery - Tsareva, Sophia A; Tsarev, Yuri V (Journal of Degraded and Mining Lands Management, 2025)
Slavneft-YANOS was one of the first in Russia to obtain the ISO 14001 compliance certificate for the Environmental Management System (EMS). This quality standard has the highest requirements for environmental management, environmental protection, and environmental safety. The paper presents the industry-specific features of the introduction of a risk-oriented approach to the EMS of oil refineries. It also uses fuzzy logic to describe analysis mechanisms and methods for assessing the risks of failure to meet the performance indicators of the EMS. The main advantage of fuzzy control in EMS is that it provides an effective means of mapping uncertainties and inaccuracies because the fuzzy logic on which control is based is identical to human thinking as opposed to traditional logical systems. Fuzzy control proves most useful as part of EMS performance analysis when processes become difficult to evaluate using common quantitative methods or when available information sources are interpreted inaccurately and uncertainly.